Identifying Raman modes of Sb2Se3 and their symmetries using angle-resolved polarised Raman spectra. Issue 17 (22nd April 2020) - Fleck, Nicole; Hobson, Theodore D. C.; Savory, Christopher N.; Buckeridge, John; Veal, Tim D.; Correia, Maria R.; Scanlon, David O.; Durose, Ken; Jäckel, Frank
Abstract : Vibrational symmetry assignments using Raman spectroscopy and density functional theory on oriented crystals also enabling orientation optimisation of thin films. Abstract : The physical properties of antimony selenide (Sb2 Se3 ) are highly anisotropic. Angle-resolved polarised Raman spectroscopy was employed to characterise oriented crystals and used in conjunction with group theory structural analysis to assign vibrational symmetries to the peaks observed in the Raman spectra. The phonon energies were corroborated via density functional theory (DFT) calculations. Furthermore, a straightforward method is proposed to verify the desirable (001) plane orientation of film growth for device applications via minimisation of the 155 cm −1 peak in the Raman spectrum.